CUSTOMARY LAW OF THE FOREST IN NORTH ACEH REGENCY - Yulia Yulia; Herinawati Herinawati (Diponegoro Law Review, 2022)
The life of woodland area management based totally on commonplace forest regulation has been practiced by the Acehnese. This pastime is done via the wooded area Pawang commonplace organization which has been shown in Aceh Qanun No. 10 of 2008 regarding Customary Institution. This has a look at uses empirical prison research with a qualitative approach the use of primary information and secondary information. In acquiring number one records, respondents and informants had been decided. The effects of research in North Aceh District, forest control based totally on commonplace wooded area regulation has not been practiced optimally. It can be visible that there are nevertheless numerous sub-districts in North Aceh that don't but have the woodland Pawang Customary Institution. Paradoxically, this sub-district has a huge forest area. Then the sub-district authorities and community leaders also do now not understand approximately the woodland Pawang commonplace organization as confirmed in the Aceh Governance regulation and the Qanun on customary institutions. The woodland Pawang customary organization additionally does now not have the capacity and information of forest management based totally on customary wooded area law, so they have no longer been maximal in carrying out their responsibilities. There are numerous limitations in forest management primarily based on Customary law by the wooded area Pawang, such as infrastructure and types of networks and local government cooperation.